Smart Cities: extra-taxation as an inducer of the development of smart cities - De Carli, Franco Guerino (2021)
This article addresses smart cities, taking into account the creation and development of human rights and sustainable development as a human right. Smart cities represent a way of promoting dignified life to their residents, as they acquire this name due to the compliance with protocols that aim at obtaining mobility, the use of technology and clean energy, the execution of actions that fairly promote social and economic development, urbanism, governance, among others. The general objective of the research is to verify the existence of a relationship between the design of smart cities and the promotion of human rights, as well as the use of extra-taxation as an inducer for the development of smart cities. To answer this question, one of the possible instruments to be used is technology, to transform urban centers into more human environments. For this, the research addresses the importance of implementing the use of Information and Communication Technologies (ICTs), present in cities called “smart”, as a way of providing more equality to city dwellers, greater dignity, and quality of life, ensuring thus making human rights of people living in urban centers more effective. To achieve these objectives, we used the hypothetical-deductive method of approach, with bibliographic and documentary research. The conclusion is that the city that manages to implement aspects of the concept of Intelligent and Human Cities provides more equality to residents, greater dignity, and quality of life, thus ensuring greater effectiveness to the human rights of people living in urban centers, with the creation of mechanisms to encourage the adoption of attitudes, by individuals, with the use of taxation − in the extra-fiscal modality.